Doença periodontal e angina pectoris estável: um estudo caso-controle - Souza, Alinne Alice Dias de Araujo (2009)
The search which it aim was to analyze the Periodontal Disease as a risk factor for the development of the Stable Angina Pectoris. For that, 120 patients (52 blokes and 68 wenches ), ages ranging from 40 to 65 years old, and attended to the Hemodinamic´s Sector of the Natal Hospital Center, showing the historic of Angina Pectoris to accomplishment of cinecoronariografhy. Before the accomplishment of this exam, the patients were submitted to interview, to investigate the possible risk factors for the Cardiovascular diseases , and it was followed of clinical periodontal examination to evaluate the presence of Periodontal Disease. After the cinecoronariography, the patients who presented diagnosis of important arterial obstruction (above 70%) were enrolled to the case grup. However the individuals with arteries free of obstruction, or obstrution below 30%, were considered without historic of Cardiovascular disease and therefore enrolled for the control grup. The groups were paired by the variables age and gender. From the analysis of the results, a did not observed statisticment the significant association between the presence of the Periodontal Disease, probing depth, periodontal attachment level, severity and extension index of the Periodontal Disease, besides the visible plaque index (VPI) an gingival bleeding index (GBI) regarding to the existence of Stable Angina Pectoris. Nevertheless , it was identified statisticment the significant association between the sistemic arterial hypertension , seric level of total cholesterol, LDL, HDL and triglycerides, showing all of them, classic risk factors appointed by the literature. Therefore, it was conclued that Periodontal Disease did not represent association with the StableAngina Pectoris at least among the studied population